WAYS TO COMBAT THE SHADOW ECONOMY IN UZBEKISTAN - Shaimanov Zhavlonbek Bakhtiyorovich; Naminova Kermen Antonovna (Antis Publisher, 2024)
The shadow sector is also expanding in certain regions of Uzbekistan, which is due to minimal control over the movement of funds carried out through the banking system to the regions. As for measures aimed at reducing the growth of the shadow sector of the economy, today this is the tightening of measures to combat corruption, the expansion of organizations involved in the fight against the illegal economy, and also, every day, underground organizations are being discovered.